Evaluating Students' Creative Thinking Skills Through E-Portfolios and Problem Based Learning - Mutiara Rahmani; Enjun Junaeti; Andini Setia Arianti (Universitas Methodist Indonesia, 2024)
According to the 2018 PISA results, Indonesian students' creative thinking skills remain low. This study aims to analyze students' creative thinking in logo design through Problem-Based Learning (PBL) using a web-based e-portfolio. The research followed the ADDIE model. In the Analysis phase, students' creative thinking needs were identified; the Design and Development phases involved constructing the PBL framework and configuring the e-portfolio platform. During the Implementation phase, students worked in groups of 3-4 over three weeks on logo design tasks, documenting their processes and receiving feedback via the e-portfolio. In the Evaluation phase, student progress was monitored, and portfolios were qualitatively assessed for improvements in creative thinking. A sample of 34 high school students was selected through convenient sampling based on class scheduling. Data were collected through questionnaires, interviews, and student portfolios and analyzed qualitatively using creative thinking dimensions of fluency, flexibility, originality, and elaboration. Overall, 50% of students’ performances across all dimensions were rated